ANALISIS PENERAPAN BIMBINGAN KELOMPOK UNTUK MEREDUKSI PERILAKU SEKS BEBAS DI KALANGAN REMAJA - Yeni Susilaningsih, Chaterina; Sri Rahayu, Dwi (Widya Warta, 2019)
Adolescents are a stage of full human development. In completing this development task, teenagers are faced with various challenges. One of the challenges faced by adolescents is tempted by promiscuity. Because at this age the individual has a high curiosity and a feeling of wanting to experiment. So that teenagers are easy to do things that are deviant, one example is free sex. Therefore, counselors have a high contribution to the development of healthy adolescents. Counselors can provide group guidance services to students on topics that discuss the effects or dangers of free sex and other information about the dimensions of human sexuality. Through group guidance services, students' knowledge of the impact or danger of premarital sexual relations increases. Students will understand the negative effects of free sex, such as pregnancy outside marriage, dropping out of school, contracting sexually transmitted diseases such as HIV/AIDS, syphilis, and the like. Furthermore, if students know and understand all the effects of free sex, students are able to distance themselves and not take actions that lead to promiscuity and free sex. The group guidance techniques that have been proven effective to improve students' understanding of the impact or danger of free sex include (1) Focus Group Discussion (FGD), (2) Modeling symbollic, (3) Discussion, (4) Bibliotherapy, (5) Tasks , (6) Home Room, and (7) Faith-Based Harmony.